Defining the genomic elements that control optic vesicle differentiation - Owen, Liusaidh (The University of Edinburgh, 2021)
Major malformations of both eyes are commonly genetically determined and a common cause of severe visual impairment in childhood. Currently, mutation in the coding region of the genome explains less than half of cases which highlights the need to define the active regulatory elements controlling the genes that cause these malformations. My thesis is focused on understanding the genetic mechanisms controlling early eye development by using a mouse organoid model to study the changes in gene expression, and regulation that control specification of the eye field and formation of optic vesicles. The first aim of my thesis addresses the transcriptomic changes over time that drive optic vesicle differentiation from mouse embryonic stem cells. I have identified a set of genes that are upregulated in the optic vesicle lineage. This list contains genes which overlap with the Xenopus eye field transcription factors, and genes which are associated with many human ocular phenotypes, as well as others not yet directly associated with eye development. I also assayed chromatin accessibility during optic vesicle organoid differentiation to identify cis-regulatory regions controlling the gene expression changes. Combining gene expression, chromatin accessibility and transcription factor binding motifs has highlighted potential regulatory elements involved in optic vesicle differentiation. I have focused on the topologically associated domains surrounding Pax6, Rax and Six6 and identified elements that are likely to regulate expression of these genes based on transcription factor footprinting and the changes in chromatin accessibility over time. Finally, I created a Pax6 knockout cell line to test how cells differentiate without a transcription factor essential for eye development. In the absence of Pax6, the cells are able to partially differentiate but do not form optic vesicles. The cells without Pax6 expression also fail to activate expression of other genes important for optic vesicle differentiation including Lhx2 and Rax. These results indicate the optic vesicle organoid system is suitable for modelling vertebrate eye development and can be useful to elucidate the gene regulatory networks controlling eye development.